Acquired colovesical fistula in a neonate: A case report - Mohamad El mahmoud; Noura Almutairi; Abdullah Alotaibi; Mohammed Alonazi; Abdullah Abduldaem; Essa Alkhodair (Elsevier, 2024)
Introduction: Colovesical fistula (CVF) is an abnormal communication between the colon and the urinary bladder, allowing fecal matter to enter the bladder. Acquired CVF are extremely rare in newborns. Case presentation: A 4-week-old male with trisomy 21 presented with septic shock and suspected necrotizing enterocolitis. Feedings were stopped and he initiated a course of intravenous antibiotics. A Foley catheter was inserted upon admission by the urology team due to difficulty with straight catheterization. It drained clear urine for approximately 20 days, after which it was removed without complications. Ten days after the removal of the Foley catheter he developed watery diarrhea and bile-stained urine, suspicious of a CVF. An abdominal X-ray revealed that the Foley catheter had entered the peritoneal cavity beyond the urinary bladder limits and showed air in the bladder. A cystourethrogram confirmed the diagnosis of a CVF. He was taken to the operating room for a cystoscopy, which confirmed a wide opening at the posterior dome of the bladder, followed by an exploratory laparotomy during which a bladder-to-sigmoid colon was identified and divided. The involved segment of the sigmoid colon was also resected. A double-barrel ileostomy was created to protect the sigmoid anastomosis. The bladder defect was closed in two layers with absorbable sutures. A Foley catheter was left in place. The patient recovered well. A cystourethrogram 10 days after the operation confirmed no leak, and the Foley catheter was removed. The ileostomy was closed 1 months after the CVF repair. Conclusion: Neonatal acquired CVF is very rare but should be suspected in patients who develop bile-stained urine and watery stool.